(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article discusses about Attracting foreign investments and establishing a conducive investment climate with guarantees for foreign investors are pivotal conditions for driving structural transformations, modernizing production, fostering export growth, and achieving import substitution in our economy.